Modulus of rupture, density and wear due to moistened and drying of compressed adobe brick with lime and/or gypsum - Depaz Blácido, Richard Alberto (2022)
This research analyzes the behavior of the modulus of rupture, the density, and the wear due to moistened and drying when including lime and/or gypsum (between 0% to 8% in 24 treatments and 2 control treatments) in the compressed adobe brick made with sifted earth from a soil clayey sand with gravel. The modulus of rupture was obtained by a test of simply loaded beam in the middle point; the density by direct measurement of dimensions and mass; the wear due to moistened and drying by five measurement cycles; and, its behavior was modeled with the geostatistical method of ordinary Kriging. Applying the Kruskal-Wallis test, and the one-factor and two-factor ANOVA, it was found that the inclusion of lime and gypsum significantly influences (p-value<α=0.05) on the increase of modulus of rupture in bending (0.660<Mr<0.925 MPa), the reduction of density (1.806≤ρ≤1.958 g/cm3), and the reduction of wear due to moistened and drying (0.00<DHS<58.92 %). Likewise, the optimal lime/gypsum ratios are 2/1 to 4/1 with a minimum of 2.0% lime and 0 to 1/5 with a minimum of 4.5% gypsum.